2017
DOI: 10.4103/ijmm.ijmm_16_157
|View full text |Cite
|
Sign up to set email alerts
|

Coagulase-negative Staphylococci: Emerging Pathogen in Central Nervous System Shunt Infection

Abstract: Central nervous system (CNS) shunts are commonly used to treat patients with hydrocephalus. Its placement is associated with increased risk of infection. The study was intended to evaluate infection rate associated with CNS shunt surgeries and identify risk factors for shunt infection. The frequency and characterisation of aetiological agents along with their antibiotic resistance pattern were also studied. A prospective study of 86 patients who underwent 97 surgeries over a period of 18 months was conducted. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 7 publications
0
5
0
1
Order By: Relevance
“…[18] It has been observed that the outcome of such patients is influenced considerably by the shunt infection itself. [19] However, many aspects of therapy are controversial because few controlled, comparative studies have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…[18] It has been observed that the outcome of such patients is influenced considerably by the shunt infection itself. [19] However, many aspects of therapy are controversial because few controlled, comparative studies have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Fibrinogen-binding proteins, such as clumping factors (Clfs) ClfA and ClfB, in addition to SdrE, result in platelet aggregation, which paves the way for endocarditis [ 48 ]. Previous research identified S. aureus as the second most common species in ventricular shunt infection [ 49 , 50 ]. Intracranial pressure and meningeal irritation were major symptoms described in cerebrospinal fluid shunt infections [ 51 ].…”
Section: Host Defense and Pathogenesis In Staphylococcus Au...mentioning
confidence: 99%
“…Methicillin-resistant Staphylococcus epidermidis is the main cause of ventriculoperitoneal shunt infection [ 3 , 8 , 11 , 18 , 19 , 23 ]. Staphylococcus aureus and Staphylococcus epidermidis are responsible for the formation of biofilm on contaminated catheters [ 19 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…
Purpose The aim of the article is to describe an immunological reaction to shunt infection in children with hydrocephalus. The main cause of shunt infection involves methicillin resistant Staphylococcus epidermidis (Bhatia et al Indian J Med Microbiol 35:120–123, 2017 ; Hayhurst et al Childs Nerv Syst 24:557–562, 2008 ; Martínez-Lage et al Childs Nerv Syst 26: 1795–1798, 2010 ; Simon et al PLoS One, 2014 ; Snowden et al PLoS One 8:e84089, 2013 ; Turgut et al Pediatr Neurosurg 41:131–136, 2005 ), a bacterial strain which is responsible for the formation of biofilm on contaminated catheters (Snowden et al PLoS One 8:e84089, 2013 ; Stevens et al Br J of Neurosurg 26: 792–797, 2012 ).
Methods The study group involved 30 children with congenital hydrocephalus after shunt system implantation, whose procedures were complicated by S .
…”
mentioning
confidence: 99%